The Relationship between Middle School Students' Mathematics Anxiety and Their Mathematical Understanding - ŞENGÜL, SARE (PEGEM AKAD YAYINCILIK EGITIM DANISMANLIK HIZMETLERI TIC LTD STI, 2018)
Development of mathematical understanding is an active process involving mathematical structures and actions. Why do students not understand mathematics? What are the reasons for that? Students have some difficulties to understand mathematics and one of them is anxiety. Mathematics anxiety is defined as an uncomfortable feeling experienced when performing a mathematical task, which is seen as an obstacle to learning mathematics. For this reason, the aim of this study was to investigate the relationship between middle school students' mathematics anxiety and their mathematical understanding. In addition to this, possible relationship was analyzed according to gender and grade levels variables. The relational screening model was used. The study was carried out with 466 middle school students. Determining the Mathematical Understanding Levels Scale and Mathematics Anxiety-Apprehension Survey were used as data collection instruments. According to the results of the study, there was a significant strong positive correlation between middle school students' mathematics anxiety and their mathematical understanding. On the other hand, the results showed no significant differences between students' mathematics anxiety and their mathematical understanding with respect to gender. However, the findings revealed significant differences in both students' mathematics anxiety and their mathematical understanding with respect to grade levels.
Keywords: Mathematics anxiety; Mathematical understanding; Relationship; Middle school students; 8TH GRADE STUDENTS; ACHIEVEMENT; PERFORMANCE; ATTITUDE